PENGARUH KEPERCAYAAN MEREK, CITRA MEREK DAN PERSEPSI KUALITAS TERHADAP LOYALITAS MEREK SENSODYNE - Ritmaratri Yola Vernadila; Reliaze Realize (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2020)
This study aimed to determine the impact of Sensodyne brand trust, brand image and perceived quality on brand loyalty. There is no doubt that brand trust, brand image and perceived quality are the most precise factors that can affect their brand loyalty. By cultivating brand trust, brand image and perceived quality will have a positive effect on their brand loyalty. The sample in the following research uses 204 customer of Sensodyne toothpaste. In gathering information on this research using a questionnaire’s distributed to customer of Sensodyne toothpaste. Diagnostic methods of data analysis are validity tests, realible tests, classic assumption tests, and hypothetical tests including t and f. For processing and analyzing analytic data in this study tool used is SPSS version 26.0. Research indicates that brand trust has a significant positive impact on brand loyalty. Brand image has a significant positive impact on brand loyalty. Perceived quality has a significant positive impact on brand loyalty. Thus at the same time brand trust, brand image and perceived quality are very practical in improving brand loyalty.